Impact of Implementation of the Core Elements of Outpatient Antibiotic Stewardship Within Veterans Health Administration Emergency Departments and Primary Care Clinics on Antibiotic Prescribing and Patient Outcomes. (7th December 2020) - Madaras-Kelly, Karl; Hostler, Christopher; Townsend, Mary; Potter, Emily M; Spivak, Emily S; Hall, Sarah K; Goetz, Matthew Bidwell; Nevers, McKenna; Ying, Jian; Haaland, Benjamin; Rovelsky, Suzette A; Pontefract, Benjamin; et al.
Abstract: Background: The Core Elements of Outpatient Antibiotic Stewardship provide a framework to improve antibiotic use. We report the impact of core elements implementation within Veterans Health Administration sites. Methods: In this quasiexperimental controlled study, effects of an intervention targeting antibiotic prescription for uncomplicated acute respiratory tract infections (ARIs) were assessed. Outcomes included per-visit antibiotic prescribing, treatment appropriateness, ARI revisits, hospitalization, and ARI diagnostic changes over a 3-year pre-implementation period and 1-year post-implementation period. Logistic regression adjusted for covariates (odds ratio [OR], 95% confidence interval [CI]) and a difference-in-differences analysis compared outcomes between intervention and control sites. Results: From 2014–2019, there were 16 712 and 51 275 patient visits within 10 intervention and 40 control sites, respectively. Antibiotic prescribing rates pre- and post-implementation within intervention sites were 59.7% and 41.5%, compared to 73.5% and 67.2% within control sites, respectively (difference-in-differences, P < .001). Intervention site pre- and post-implementation OR to receive appropriate therapy increased (OR, 1.67; 95% CI, 1.31–2.14), which remained unchanged within control sites (OR, 1.04; 95% CI, .91–1.19). ARI-related return visits post-implementation (–1.3% vs –2.0%; difference-in-differences P = .76) were not different, but all-cause hospitalization was lower within intervention sites (–0.5% vs –0.2%; difference-in-differences P = .02). The OR to diagnose non-specific ARI compared with non-ARI diagnoses increased post-implementation forintervention (OR, 1.27; 95% CI, 1.21 –1.34) but not control (OR, 0.97; 95% CI, .94–1.01) sites. Conclusions: Implementation of the core elements was associated with reduced antibiotic prescribing for RIs and a reduction in hospitalizations. Diagnostic coding changes were observed. Abstract : A multicentered intervention based on the Core Elements of Antibiotic Stewardship was conducted to improve outpatient acute respiratory tract infection management. Intervention was associated with reduced antibiotic prescribing and reductions in hospitalization.